Direct chemical synthesis of ultrathin holey iron doped cobalt oxide nanosheets on nickel foam for oxygen evolution reaction. (December 2018) - Li, Ying; Li, Fu-Min; Meng, Xin-Ying; Wu, Xin-Ru; Li, Shu-Ni; Chen, Yu
Abstract: The oxygen evolution reaction (OER) on the anode is a vital electrocatalytic reaction in the field of energy conversion. Currently, transition metals-based nanomaterials are promising Ir/Ru-alternative OER electrocatalysts in alkaline media. In this work, we report that in-situ direct growth of atomically thick Fe doped Co3 O4 holey nanosheets on nickel foam (Fe-Co3 O4 H-NSs/NF) using a simple cyanogel−NaBH4 route, which effectively avoids the tedious post-etch process of nanosheets using plasma, acid, alkali, and so on. Benefiting from ultrathin thickness (1.5 nm), numerous holes, and synergistic effect between Co and Fe atoms, Fe-Co3 O4 H-NSs/NF provide a large specific surface area (199.12 m 2 g −1 ) and highly active catalytic sites for the OER. Meanwhile, nickel foam substrate with three-dimensionally porous structure and high conductivity accelerates molecules/ions/gases transportation and electron transfer. Consequently, Fe-Co3 O4 H-NSs/NF with optimal Co/Fe composition show super electrocatalytic performance for the OER, including an overpotential as small as ∼204 mV at 10 mA cm −2 current density and a small Tafel slope of 38 mV dec −1, which is much better than commercial RuO2 nanoparticles. Graphical abstract: Highlights: Fe-Co3 O4 H-NSs/NF are obtained by a simple cyanogel−NaBH4 route. Co III -Co II cyanogel precursor plays a key role for Fe-Co3 O4 H-NSs/NF formation. The thickness of Fe-Co3 O4 H-NSs is only ca. 1.5 nm. Fe-Co3 O4 H-NSs/NF with abundant pores own the high surface area and numerous defected atoms. Fe-Co3 O4 H-NSs/NF have a very small overpotential for the oxygen evolution reaction in the alkaline media.